Constructing compact representations of ambiguous language - VOGEL, CARL (My University, 1997)
An application of DRT to the development of a computational semantics for a broad coverage fragment of German is described The archi tecture of the system is inuenced by human use of natural language in that initial process ing is a fast but shallow process For any sen tence in the fragment a single representation is constructed from which exactly the appropriate disambiguations can be enumerated or reasoned with directly if full analysis isnt essential The representational assumptions are outlined as is the scope of the current coverage in the semantic fragment and its implementation. We detail the semantic analysis assumed for questions
PUBLISHED
Keywords: DRT